E-Cigarette Explosions and Burns - Sai Sirikonda; Laura Cappuyns; Liby Philip; Katie Hirst; Dilnath Gurusinghe; Kayvan Shokrollahi (Annals of Plastic Surgery, 2026)
Introduction: The use of electronic nicotine delivery systems (ENDS) has increased globally, particularly among younger populations, despite ongoing safety concerns. Although promoted as a safer alternative to smoking, ENDS have been associated with burn injuries secondary to device explosions, most commonly due to lithium-ion battery failure. The true incidence, injury patterns, and management strategies for these burns remain poorly defined in the literature. Methods: A retrospective review was conducted for patients presenting with ENDS-related burn injuries at a regional burns center in the UK between January 2015 and December 2025. Cases were identified through the International Burns Injury Database (IBID) using predefined search terms and manually screened to confirm eligibility. The data collected included patient demographics, burn characteristics, management, and clinical outcomes. Results: A total of 47 patients with ENDS-related burn injuries were identified (mean age: 40 y; 87% male). Injuries most commonly occurred when devices were not in use (94%), typically in the trouser pocket (81%). Burns predominantly affected the thigh (77%) and hand (23%), with a mean TBSA of 2.34% (SD: 1.79). Most injuries were partial- or mixed-depth burns. The majority of patients were managed conservatively (77%); however, 36% required hospitalization and 23% underwent surgery. Complications occurred in 14% of the cases, with 9% required further surgery. Conclusion: ENDS-related explosions represent an underrecognized mechanism of burn injury, often occurring when devices are not in use and frequently require hospitalization or surgical intervention. Enhanced public awareness, improved device safety, and stronger regulatory standards are required to reduce the burden of these injuries.